The potential of pro-market activism as a tool for making finance work for Africa: a political economy perspective - Florence Dafe (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Under what conditions can government interventions in the financial sector be a successful tool to increase the financial resources available for productive investment in sub-Saharan Africa? This is the question which drives this paper. Historically and in line with welfare economic theory market failures have provided an argument for activism, defined as deliberate government interventions in the financial sector to promote the delivery of financial services to segments of the private sector that are underserved. The experience with activism has been mixed at best. However, even though activism does not guarantee an increase in broad-based productive private investment, past experience suggests that achieving this goal without deliberate government interventions is difficult, if not impossible. This paper proposes a political economy perspective to explore under what conditions government interventions in financial markets could promote finance for development. The study seeks to contribute towards developing a political economy framework which helps evaluating ex ante whether a government in a particular country has good enough governance to assume a more activist role in financial sector development.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Governance